A novel mutation within gene in a young girl with hypophosphatemic rickets and review of literature - Chong Kun Cheon; Hoon Sang Lee; Su Yung Kim; Min Jung Kwak; Gu-Hwan Kim; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2014)
X-linked hypophosphatemia (XLH) is the most common form of familial hypophosphatemic rickets and it is caused by loss-of-function mutations in the PHEX gene. Recently, a wide variety of PHEX gene defects in XLH have been revealed; these include missense mutations, nonsense mutations, splice site mutations, insertions, and deletions. Recently, we encountered a 2-year-9-month-old female with sporadic hypophosphatemic rickets. She underwent osteotomy, dental abscess was evident, and there was severe bowing of the legs. A low serum phosphorus level in combination with elevated serum alkaline phosphatase activity and normal serum calcium is suggestive of hypophosphatemic rickets. PHEX gene analysis revealed a splice acceptor site mutation, c.934-1G>T (IVS8-1G>T), at the intron8 and exon9 junction. To the best of our knowledge, this mutation is novel and has not been reported. The results of this study expand and improve our understanding of the clinical and molecular characteristics and the global pool of patients with sporadic hypophosphatemic rickets.